Stabilization of soybean oil-in-water emulsions using polypeptide multilayers: Cationic polylysine and anionic polyglutamic acid. (November 2020) - Muriel Mundo, Jorge L.; Zhou, Hualu; Tan, Yunbing; Liu, Jinning; McClements, David Julian
Graphical abstract: Highlights: Oil droplets were coated by polypeptide multilayers via electrostatic deposition. Anionic saponin-coated lipid droplets were used as initial templates. Cationic polylysine & anionic polyglutamic acid were used as polypeptides. The impact of pH, salt, & heat on emulsion stability were measured. Single-layer emulsions were more stable than multilayer ones. Abstract: Oil-in-water emulsions are used as delivery systems for non-polar functional ingredients in various industries, including foods, cosmetics, personal care products, agrochemicals, and pharmaceuticals. Emulsions, however, tend to breakdown under the conditions found in many commercial products. In this study, the functional performance of the lipid droplets in emulsions was tailored by sequential layer-by-layer electrostatic deposition of oppositely charged polypeptides onto their surfaces. Cationic poly-L-lysine (PLL) and anionic poly-glutamic acid (PGA) were used as a pair of oppositely charged polypeptides (pH 4.0). First, a primary emulsion (10% w/w soybean oil-in-water emulsion) was formed consisting of small lipid droplets ( d32 = 500 µm) coated by a natural surfactant (0.05% w/w quillaja saponin). Second, cationic PLL was deposited onto the surfaces of the anionic saponin-coated droplets. Third, anionic PGA was deposited onto the surfaces of the cationic PLL-saponin-coated droplets. We then assessed the ability of the coatings to protect the lipid droplets from aggregation when the pH (2.0–9.0), ionic strength (0–350 mM), or temperature (30–90 °C) were altered. The properties of the primary, secondary, and tertiary emulsions were monitored by measuring the mean particle diameter (d32 ), electrical characteristics (ζ-potential), and microstructure of the lipid droplets. The electrical characteristics of the droplets could be modulated by controlling the number and type of layers used. The primary emulsion had the best resistance to varying environmental conditions, while the secondary emulsion had the worst, suggesting electrostatic deposition should only be used to obtain specific functionalities. Interestingly, PLL detached from the surfaces of the secondary emulsions at high salt concentrations due to electrostatic screening, which improved their salt stability. This phenomenon may be useful for some food applications, e.g., having cationic droplets during food storage, but anionic ones inside the human body.